Effect of Aid for Trade and Foreign Direct Investment Inflows on the Utilization of Unilateral Trade Preferences offered by the QUAD countries - Sèna Kimm Gnangnon; Harish Iyer (ZBW - Leibniz Information Centre for Economics, 2021)
Development aid and non-reciprocal trade preferences (NRTPs) are two major tools available to wealthier nations to assist developing countries in their development efforts. The present paper investigates the effect of Aid for Trade (AfT) flows (that are key for the integration of developing countries into the global trading system) and foreign direct investment (FDI) inflows, as well as their interplay on the utilization of NRTPs offered by the Quadrilaterals (i.e., QUAD countries). Two major blocks of NRTPs provided by the QUAD countries have been considered, namely the Generalized System of Preferences (GSP) programs and other NRTPs. The analysis has covered 114 beneficiary countries of these NRTPs (of which 38 Least developed countries - LDCs) and the period 2002-2018. Several findings have emerged from the analysis. Over the full sample, total AfT flows contribute to enhancing the utilization rate of both GSP programs and other NRTPs. FDI inflows influence positively the utilization rate of both GSP programs and other NRTPs, with the effect on the former being higher than the effect on the latter. For LDCs, total AfT flows are associated with a better utilization of GSP programs at the expense of other NRTPs, while for NonLDCs, total AfT flows generate a better utilization of GSP programs compared to other NRTPs. In the meantime, higher FDI inflows improve the utilization of the two types of NRTPs, although they exert a higher positive effect on the utilization of GSP programs than on that of other NRTPs. In NonLDCs, higher FDI inflows contribute to improving the utilization of GSP programs, but lead to a lower degree of usage of other NRTPs. Total AfT flows and FDI inflows are strongly complementary in affecting positively the utilization of both types of NRTPs, and the degree of this complementarity is higher on the utilization of other NRTPs than on the utilization of GSP programs. Finally, beneficiary countries' level of export product diversification matters for the effect of both AfT flows and FDI inflows on the utilization of NRTPs. The conclusion section discusses the implications of these findings.
Keywords: F13; F14; F13; 330; Aid for Trade; Foreign Direct Investment Inflows; Non-reciprocal trade preferences utilization; QUAD countries; Developing Countries